Modernisation Issues of Diesel-Electric Shunting Locomotive Power Units - Hoimoja, Hardi; Jalakas, Tanel; Rosin, Argo; Rassylkin, Anton (Electrical, Control and Communication Engineering, 2010)
The research concentrates on the modernisation issues of inefficient diesel-electric shunting locomotives, produced in the former Soviet Union. The existing diesel-generator unit, serving as an onboard power plant can be replaced by hybridised units, with an energy storage unit acting as a peaking power source for dynamic modes. By integrating an energy storage unit into the power plant, the locomotive traction drive becomes hybridised, consuming less fuel during transients and idling.